Bromus husainii (Poaceae:Bromeae), a new species from Valley of Flowers National Park, Uttarakhand, India - Yadav, Rekha; Prasad, Dileshwar; Tripathi, Shailja; Jaiswal, Shubham; Agnihotri, Priyanka (Phytotaxa, 2021)
Bromus husainii, a new species of Poaceae collected from Valley of Flowers National Park, Uttarakhand, is described and illustrated. The new species is closely related to B. confinis in having similar rhizomatous habit and purple-tinged spikelets but differs by the characters of inflorescence with heteromorphic spikelets and a band of hairs present on its collar. Moreover, presence of robust spikelets make it different from other species of Bromus.